Молекулярні механізми розвитку діабетичної мікроангіопатії - Burlaka, A.P.; Ganusevych, I.I.; Sydoryk, E.P.; Tronko, K.M.; Naumenko, V.G.; Tronko, M.D. (Ендокринологія | Endokrynologia, 2012)
Молекулярні механізми розвитку діабетичної мікроангіопатії